Spontaneous antibodies against Engrailed‐2 (EN2) protein in patients with prostate cancer. (August 2014) - Annels, N. E.; Simpson, G. R.; Denyer, M.; McGrath, S. E.; Falgari, G.; Killick, E.; Eeles, R.; Stebbing, J.; Pchejetski, D.; Cutress, R.; Murray, N.; Michael, A.; et al.
Summary We reported the expression of the homeodomain‐containing transcription factor Engrailed‐2 (EN2) in prostate cancer and showed that the presence of EN2 protein in the urine was highly predictive of prostate cancer. This study aimed to determine whether patients with prostate cancer have EN2 autoantibodies, what the prevalence of these antibodies is and whether they are associated with disease stage. The spontaneous immunoglobulin (Ig)G immune response against EN2 and for comparison the tumour antigen New York Esophageal Squamous Cell Carcinoma 1 (NY‐ESO‐1), were tested by enzyme‐linked immunosorbent assay (ELISA) in three different cohorts of prostate cancer patients as well as a group of men genetically predisposed to prostate cancer. Thirty‐two of 353 (9·1%) of the SUN cohort representing all stages of prostate cancer demonstrated EN2 IgG responses, 12 of 107 patients (11·2%) in the advanced prostate cancer patients showed responses, while only four of 121 patients (3·3%) with castrate‐resistant prostate cancer showed EN2 autoantibodies. No significant responses were found in the predisposed group. Anti‐EN2 IgG responses were significantly higher in patients with prostate cancer compared to healthy control males and similarly prevalent to anti‐NY‐ESO‐1 responses. While EN2 autoantibodies are not a useful diagnostic or monitoring tool, EN2 immunogenicity provides the rationale to pursue studies using EN2 as an immunotherapeutic target.